The important role of concurrent engineering in product development process - Hambali, Ariff; Salit, Mohd Sapuan; Ismail, Napsiah; Yusoff, Nukman; Abdul Karim, M. S. (Universiti Putra Malaysia Press, 2009)
Nowadays, Concurrent Engineering (CE) is becoming more important as companies compete in the worldwide market. Reduced time in product development process, higher product quality, lower cost in manufacturing process and fulfilment of customers' requirements are the key factors to determine the success of a company. To produce excellent products, the concept of Concurrent Engineering must be implemented. Concurrent Engineering is a systematic approach which can be achieved when all design activities are integrated and executed in a parallel manner. The CE approach has radically changed the method used in product development process in many companies. Thus, this paper reviews the basic principles and tools of Concurrent Engineering and discusses how to employ them. Similarly, to ensure a product development process in the CE environment to run smoothly and efficiently, some modifications of the existing product development processes are proposed; these should start from market investigation to detail design.